MEJORANDO LA CALIDAD DE LA INVESTIGACIÓN POR MEDIO DE ENCUESTAS EN LOS PAÍSES EN DEMOCRATIZACIÓN - Seligson, Mitchell A. (2023)
The rise of democracies in the developing world has produced a boom in the field of survey research. Unfortunately, researchers in both scholarly and applied settings often incorrectly assume that the data being generated in the developing world are of the same quality as that from first world sources. In fact, as this article shows, there is reason to be very concerned about the quality of the data emerging from those surveys. Using poor quality data inevitably leads to a greater incidence of “Type II” errors by which a null hypothesis (i.e., that there exists no significant relationship among a given set of variables) is falsely accepted.  The survey research community must take three steps to overcome these problems:  set standards, insist on archiving of data sets, and form greater human capital.